2018
DOI: 10.4172/2473-3350.1000256
|View full text |Cite
|
Sign up to set email alerts
|

What Factors Influence the Persistence of Female Genital Mutilation in Nigeria ? A Systematic Review

Abstract: Background: Female Genital Mutilation is the excision of any part of the female genital organs for non-medical reasons. According to the World Health Organization, approximately 200 million girls and women have been mutilated around the world. This practise is strongly tied to different cultural traditions. FGM has called for international recognition due to its violation of human rights. Over the past decades, there have been deliberations by researchers concerning the practice of FGM. Some have tried to unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…The findings this study are in line with what have been reported by other studies which observed that FGM was largely practiced in communities for conformity to cultural and traditional beliefs, and norms including FGM being perceived as rite of passage for girls to womanhood and that it enhance chastity and purity making girls more marriageable. 20 , 16 , 21 Similar to the findings of this study, Reig Alcaraz et al 22 and Ogoe 4 also noted that the need to conform to traditional cultural beliefs that supported FGM remained a leading reason for the continued practice of FGM in many settings across the globe. The findings of this study support the observations made by Moranga 15 which attributed the persistence of FGM practice in one of Kenya's communities to FGM being used as a symbol of ethnic identity, a community mobilization tool and it being associated with feminine beauty and cleanliness.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The findings this study are in line with what have been reported by other studies which observed that FGM was largely practiced in communities for conformity to cultural and traditional beliefs, and norms including FGM being perceived as rite of passage for girls to womanhood and that it enhance chastity and purity making girls more marriageable. 20 , 16 , 21 Similar to the findings of this study, Reig Alcaraz et al 22 and Ogoe 4 also noted that the need to conform to traditional cultural beliefs that supported FGM remained a leading reason for the continued practice of FGM in many settings across the globe. The findings of this study support the observations made by Moranga 15 which attributed the persistence of FGM practice in one of Kenya's communities to FGM being used as a symbol of ethnic identity, a community mobilization tool and it being associated with feminine beauty and cleanliness.…”
Section: Discussionsupporting
confidence: 82%
“…4 , 13 , 14 Among factors cited to contribute to this harmful practice in the East African region include its social acceptance, low level of awareness about its harmful impact on the health of women and girls, cultural beliefs and traditions, ignorance on women's reproductive health issues among local communities and beliefs that FGM leads to increased pleasure for male partners, enhanced fertility and improved marriage prospects. 4 , 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
“…A previous study shows that mothers' intentions and perceived benefits of FGM underlie their intention to practice genital mutilation [ 14 ]. This may relate to mothers who ascribe sexual purity to FGM and for them, performing FGM on their daughters could help them to maintain the 'legacy' of sexual purity [ 15 , 16 ]. Where mothers who were themselves mutilated in turn expose their daughters to the same mutilation process, this is referred to as generational continuation of FGM in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond this theoretical postulation, it might be reasoned that some mothers who underwent FGM might find it harmful and thus refuse to extend it to their daughters. However, available evidence from Nigeria shows that there are factors that might make women to expose their daughters to FGM despite the harms posed by the practice [ 14 16 ]. For instance, many girls/women are made to undergo FGM out of fear of stigmatisation and rejection in their communities [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation